Assessment of Early Childhood Education Programme Implementation by Pre-schools during COVID-19 Lockdown in Nigeria. - Okunaiya, Gbone Adunola; Olajide, Simeon Olayinka (Journal of Education and Practice, 2023)
Purpose: The study assessed the implementation process of early childhood education in distance learning during the Covid-19 lockdown in Osun State. It also determined the delivery system for distance pre-school education during the Covid-19 lockdown in the study area and examined the challenges of distance learning in early childhood education during the Covid-19 lockdown in the study area. These were done with a view to providing empirical information on the implementation process of early childhood education in distance learning during the Covid-19 lockdown in Osun State. Methodology: The study adopted a descriptive research design. The population consisted of all the early childhood administrators of pre-primary schools in Osun state. The sample comprised 30 early childhood education centres selected across the three senatorial districts in the state. Multi-stage sampling procedure was used to select the sample for the study. For the three senatorial districts, one local government area (LGA) was selected using simple random sampling technique. From each LGA, ten early childhood education centres were selected using simple random sampling techniques. All schools that had preschool sections and accepted to participate in the study were involved. From each preschool centre an administrative head/representative was selected using simple random sampling technique. One research instrument was used titled; "˜Pre-schoolers Centers Covid-19 Lockdown Assessment Questionnaire (PCCAQ). Pearson Product Moment Correlation Statistics was used to calculate the reliability of the PCCAQ and was found to be 0.71. Data collected were analysed using frequency counts and simple percentages. Findings: The result in the study showed that the implementation process for distance learning during the covid-19 lockdown was poor with 80.0% of the preschoolers' centres did not implement distance learning during covid-19 lockdown. In addition, results revealed that the delivery system for distance pre-school education during covid-19 lockdown in the study area was very poor with 70.0% of preschool centres not organising distance learning during the period of the lockdown. Unique Contribution to Theory, Policy and Practice: Finally, the result showed that 66.7% of the pre-school centres were having challenges in engaging children during the period of the lockdown. The study concluded that early childhood education programmes by pre-schools during covid-19 lockdown in Osun state were not implemented.